Time-varying outcomes associated with maternal age at first birth - Fulco, Celia J., author; Rickard, Kathryn, advisor; Henry, Kimberly, committee member; Yuma, Paula, committee member (Colorado State University. Libraries, 2018)
Those who become mothers early in life face poorer outcomes related to social, economic, educational, and health factors for both mother and child. The literature often uses teenage and "early" parenting interchangeably as predictors of associated outcomes. However, changing the operational definition of early motherhood to include those who are 19 and under, 22 and under, or 25 and under does not significantly alter results that show younger mothers having worse economic outcomes, comparatively (Gibb, Fergusson, Horwood, & Boden, 2014). In response to the tendency of using age at first birth as a categorical predictor of outcomes, the time-varying relationship between maternal age at first birth and socioeconomic and parenting outcomes was examined using longitudinal data. A time-varying effect model was employed to display average level of education, home/parenting quality scores, and the odds of poverty as a function of maternal age at first birth, controlling for race/ethnicity and having the father in the child's household. We used data from a national longitudinal study of mothers who participated in the Child and Young Adult cohort of the National Longitudinal Survey of Youth. Peak scores for all outcomes were observed around maternal age of 30 for all three initial models. Parenting and home quality gradually improved until late 20's when scores appeared to level out throughout the 30's. Highest grade completed increased until just after age 30 then dipped again around age 40. The odds of poverty decreased until about age 30 then leveled out. Controlling for father's presence in the household and race/ethnicity shifted all three selected effects. Overall, earlier maternal age at first birth was associated with incrementally decreasing parenting and home quality, lower educational attainment, and greater likelihood of poverty status. The results highlight the problematic nature of utilizing categorical (e.g., teenage vs. non-teenage) age groups to predict maternal and child outcomes. In fact, results of this study suggest that optimal socioeconomic and parenting outcomes level out around age 30 for this nationally representative sample. Current trends in psychological, developmental, and economic research should consider curvilinear patterns of outcomes related to maternal age at first birth rather than relying on categorical comparisons of age groups.
Keywords: maternity; poverty; parenting; education